DPPG2-based thermosensitive liposomes as drug delivery system for effective muscle-invasive bladder cancer treatment in vivo. (1st January 2021) - Brummelhuis, Iris S. G.; Simons, Michiel; Lindner, Lars H.; Kort, Simone; de Jong, Sytse; Hossann, Martin; Witjes, J. Alfred; Oosterwijk, Egbert
Abstract: Purpose: Recommended treatments for muscle-invasive bladder cancer (MIBC) come with considerable morbidity. Hyperthermia (HT) triggered drug release from phosphatidylglycerol-based thermosensitive liposomes (DPPG2 -TSL) might prevent surgical bladder removal and toxicity from systemic chemotherapy. We aimed to assess the efficacy of DPPG2 -TSL with HT in a syngeneic orthotopic rat urothelial carcinoma model. Methods: A total of 191 female Fischer F344 rats were used. Bladder tumors were initiated by inoculation of AY-27 cells and tumor-bearing rats were selected with cystoscopy and semi-randomized over treatment groups. On days 5 and 8, animals were treated with DOX in different treatment modalities: intravenous (iv) DPPG2 -TSL-DOX with HT, iv free DOX without HT, intravesical DOX without HT, intravesical DOX with HT or no treatment (control group), respectively. Animals were euthanized on day 14 and complete tumor response was assessed by histopathological evaluation. Results: Iv DPPG2 -TSL-DOX + HT resulted in a favorable rate of animals with complete tumor response (70%), compared to iv free DOX (18%, p  = .02), no treatment (0%, p  = .001), and intravesical DOX with (43%, p  = .35) or without HT (50%, p  = .41). All rats receiving intravesical DOX with HT and 24% of rats treated with DPPG2 -TSL-DOX containing the same DOX dose with HT had to be euthanized before day 14 because of substantial bodyweight loss, which was associated with dilated ureters urine retention in a few rats. Conclusion: Treatment with DPPG2 -TSL-DOX combined with intravesical HT outperformed systemic and intravesical DOX in vivo . There might be a role for DPPG2- TSL encapsulating chemotherapeutics in the treatment of MIBC in the future.